The Concept of Sustainable Development of the Oil and Gas Sector as One of the Subsystems of Noonomics - A. S. Fomenko (Ekonomika Nauki)
This work is devoted to the study of a new way of development of the oil and gas industry, which is due to the influence of many factors of our time. Factors such as limited resources, an increase in the anthropogenic and technological load on the environment, and the risks associated with the complexity of the oil refining process itself, require a fundamentally different solution, which is fully provided by noonomics. It is shown that sustainable development based on the principles of noonomics reduces the role and significance of material factors in the production process of vertically integrated oil companies and the oil and gas industry as a whole, highlighting scientificand technological progress in oil and gas production and their processing.